Early rapid local impedance drop is associated with acute lesion efficacy during pulmonary vein isolation using a novel contact force sensing catheter. (3rd October 2022) - Perge, P; Sallo, Z; Petrovic, N; Piros, K; Nagy, K V; Osztheimer, I; Merkely, B; Geller, L; Szegedi, N
Abstract: Introduction: The predictive role of adequate local impedance drop in lesion formation using a novel contact force sensing ablation catheter for pulmonary vein isolation was recently described. The purpose of our study was to assess the temporal characteristics of local impedance drop during ablation and its correlation with acute lesion efficacy. Methods: Point-by-point radiofrequency pulmonary vein isolation was performed in power-controlled mode with 50 W energy setup. The efficacy of applications was determined by pacing along the circular ablation line. The successful lesions were estimated if loss of capture was achieved. Local impedance, contact force and catheter position data of the applications with 5 msec resolution was analysed. The local impedance of successful and unsuccessful applications was compared at baseline and 2, 4, 6, 8, 10 and 12 sec time points, respectively. We characterized the local impedance for each time point with the mean of the 5 impedance value closest in time. The sum of the range of catheter position in x, y and z dimensions was also compared to assess stability during the application. Results: 643 applications were analysed, 559 were successful and 84 were unsuccessful. Mean contact force was lower (p=0.04), while the sum of catheter position range was higher (p<0.001) in unsuccessful applications during ablation, suggesting worse catheter stability. The successful applications were characterized by a higher baseline local impedance (p<0.001), and a larger local impedance drop at the 2, 4, 6, 8 and 10 sec time points (p<0.001, for all). In case of unsuccessful applications, after a moderate but significant drop from baseline to the 2 sec time point (baseline: 153 Ohm vs 2 sec: 145 Ohm, p<0.001) local impedance did not change further over time (2 sec: 145 Ohm vs 12 sec: 143 Ohm; p=0.99). While on the other hand, in case of successful applications, the local impedance further decreased significantly up to the 10 sec timepoint, respectively (baseline: 161 Ohm vs 2 sec: 150 Ohm vs 10 sec: 141 Ohm, p<0.001 for all). The optimal cut-point for the local impedance drop indicating unsuccessful application was <9 Ohms at the 4 second time point [AUC=0.73 (0.67–0.76), p<0.001]. Failing to reach at least 9 Ohm impedance drop at the 4 second time point predicted unsuccessful applications [(p<0.001; OR: 3.82 (2.34–6.25)]. Conclusion: Rapid and enduring drop of the local impedance may predict effective lesion formation, while slightly changing or unchanged local impedance is associated with unsuccessful applications. In case of a moderate local impedance drop during the first 4 seconds of radiofrequency application, it might be reasonable to stop the application and start a new one after catheter repositioning. Funding Acknowledgement: Type of funding sources: None.